2023
DOI: 10.3390/membranes13060540
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism Reprogramming and Trastuzumab Resistance in Breast Cancer Cell Lines Overexpressing the ERBB2 Membrane Receptor

Abstract: Trastuzumab (Tz), an antibody targeting ERBB2, has significantly improved the prognosis for breast cancer (BCa) patients with overexpression of the ERBB2 receptor. However, Tz resistance poses a challenge to patient outcomes. Numerous mechanisms have been suggested to contribute to Tz resistance, and this study aimed to uncover shared mechanisms in in vitro models of acquired BCa Tz resistance. Three widely used ERBB2+ BCa cell lines, adapted to grow in Tz, were examined. Despite investigating potential change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Thus, several studies have reported the existence of alterations in mitochondrial function as well as alterations in the metabolism of cells that exhibit resistance to tamoxifen [ 81 , 82 ]. Regarding the development of trastuzumab resistance, several metabolic alterations have been identified: increased glycolysis by HSF1 and LDH-A contributes to the development of trastuzumab resistance [ 22 ]; activation of t-DARPP and IGF-1R in the stimulation of glycolysis confers resistance to trastuzumab [ 83 ]; and the development of resistance to anti-HER2 therapies has also been associated with the reprogramming of lipid metabolism [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies have reported the existence of alterations in mitochondrial function as well as alterations in the metabolism of cells that exhibit resistance to tamoxifen [ 81 , 82 ]. Regarding the development of trastuzumab resistance, several metabolic alterations have been identified: increased glycolysis by HSF1 and LDH-A contributes to the development of trastuzumab resistance [ 22 ]; activation of t-DARPP and IGF-1R in the stimulation of glycolysis confers resistance to trastuzumab [ 83 ]; and the development of resistance to anti-HER2 therapies has also been associated with the reprogramming of lipid metabolism [ 84 ].…”
Section: Discussionmentioning
confidence: 99%